Analogue forestry : an introduction - Senanayake, Ranil (Monash publications in geography, 1998)
"Analogue forestry is a reponse that seeks to address both the genetic and the cultural issues of biological loss. This paper explores the major ecological process that underlie Analogur Forestry" -- p.vii.